Pedro de Valencia. Obras completas VIII. Epistolario, Jesús Mª Nieto Ibáñez, Inmaculada Delgado Jara y Mª Isabel Viforcos Marinas (coordinadores), León, Universidad de León, 2019, 635 pp. ISBN 978-84-9773-966-5 (Minerva, 2019)
Review: Pedro de Valencia. Obras completas VIII. Epistolario, Jesús Mª Nieto Ibáñez, Inmaculada Delgado Jara y Mª Isabel Viforcos Marinas (coordinadores), León, Universidad de León, 2019, 635 pp. ISBN 978-84-9773-966-5